2021
DOI: 10.1002/adem.202001471
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Acoustic Behavior of 3D‐Printed Hierarchical Mathematical Fractal Menger Sponge

Abstract: Structural materials that feature hierarchical architectures (e.g., fractals) display remarkable mechanical properties. Menger sponge is one of the fractal geometries defined in Mathematics and made up of a unit cube with three orthogonal cavities. The precise fractal dimensions are fabricated using 3D printing. Experiments and simulations are conducted on the structure under uniaxial compression. The effect of increasing the levels of orthogonal cavities of the Menger sponge structure as well as the changing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…As shown, the E eff values obtained for Menger pre-fractal sponge of Ti-6Al-4V alloy using Xie's approach fitted quite well to the Gibson and Ashby model with n = 2 (Figure 9). However, slopes proximal to n = 1 were reported in porous parts with the conventional formation sequence of Menger sponge but made of NiTi alloy (Zhao et al , 2021) and PLA (Kushwaha et al , 2021). In NiTi parts, Zhao et al (2021) reported stress-induced martensite transformation during the compressive testing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown, the E eff values obtained for Menger pre-fractal sponge of Ti-6Al-4V alloy using Xie's approach fitted quite well to the Gibson and Ashby model with n = 2 (Figure 9). However, slopes proximal to n = 1 were reported in porous parts with the conventional formation sequence of Menger sponge but made of NiTi alloy (Zhao et al , 2021) and PLA (Kushwaha et al , 2021). In NiTi parts, Zhao et al (2021) reported stress-induced martensite transformation during the compressive testing.…”
Section: Discussionmentioning
confidence: 99%
“…The stretch deformation predominates for high values of N . PLA parts with similar pore architecture also presented a similar deformation behavior in the pores independently of their size, involving a bending of horizontal struts in the direction of applied force (Kushwaha et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, 3D printing is the finest technique to fabricate complex porous geometry due to design freedom and sustainability. [10][11][12][13][14][15] Development of structures with dual nature of deformation (hard and soft) is a challenge; therefore, mainly researchers prefer multimaterials, [16] blends/alloys, [17] and composites, [18] but then the interface of such a system becomes vulnerable. Sajadi et al demonstrated unique mechanical properties (strength, modulus, and impact resistance) in 3D-printed complex schwarzites structures (such as primitive and gyroid structure).…”
Section: Introductionmentioning
confidence: 99%